THE CLIMATIC INTERPRETATION OF PAN-EUROPEAN SIGNATURE YEARS IN OAK RING-WIDTH SERIES - Kelly P.M.; Leuschner H.H.; Briffa K.R.; Harris Ia.C. (My University, 2002)
Large-scale signature years, in which oak growth across much of northern Europe varies consistently, are identified. Postulating that the likely cause of such widespread departures in growth is climatic, it is shown that these years were characterized by pan-European anomalies in soil-moisture availability, rainfall and temperature, with enhanced growth associated with an extended period of increased soil-moisture availability and reduced growth associated with lower temperatures and reduced soil moisture. These climatic anomalies are, in turn, associated with a large-scale and persistent perturbation in the atmospheric circulation that involves the circumpolar vortex and appears related to the Arctic Oscillation. The 2000-year record of signature-year occurrence shows variations in frequency at the decadal and century levels. It is necessary to interpret this record with caution. Nevertheless, these results do confirm earlier suggestions that large-scale climatic information is contained in regional composite archaeological chronologies. With supporting evidence from other sources, it should be possible to extract useful proxy climate data, even though the precise provenance of the timbers from which the records were derived might not be known.
Keywords: DENDROCLIMATOLOGY; TREE RINGS; SIGNATURE YEARS; SOIL MOISTURE; QUERCUS SPP; EUROPEAN CLIMATE; LATE HOLOCENE; ARCTIC OSCILLATION